Improved Light Management in Silicon Heterojunction Solar Cells by Application of a ZnO Nanorod Antireflective Layer. (August 2016) - Ahrlich, Maike; Sergeev, Oleg; Juilfs, Maren; Neumüller, Alex; Vehse, Martin; Agert, Carsten
Abstract: This study reports successful application of ZnO nanorod arrays for efficient reduction of reflection losses in heterojunction solar cells on flat non-textured silicon wafers. In addition, aluminium doped zinc oxide (AZO) is proposed as a cheap, abundant and environment-friendly substitution for indium doped tin oxide (ITO), commonly used in transparent front electrodes. The results show a significant reduction of the average weighted cell reflectivity and hence an enhancement in the external quantum efficiency and in the short circuit current density. The main antireflective mechanism was found to be a grading of the refractive index at the AZO/air interface, which has been shown by optical simulations describing the nanorod layer as an effective medium. The ZnO nanorod layers were grown by electrochemical deposition, which is a low-cost and industrially applicable method, since no vacuum conditions and high temperatures are required. Therefore, this concept could be a promising process step in the photovoltaic industry to improve light management in silicon heterojunction solar cells with AZO front contacts, especially attractive for the production utilizing very thin wafers, where wafer texturing for antireflection purposes shows important drawbacks.